A Note on the Compound Kabul/ Zirang-China/ Chinestan Based on Kush-nama - Daryoosh Akbarzadeh (مجله مطالعات ایرانی, 2021)
1.Introduction Kuš-nāma (501-04/1108-11) is one of the most important books dealing with Iran-China and Silla historical relations. A unique manuscript of the work (by M. Abullah-al-Qari) is found in a collection held in the British Library (OR 2780). The manuscript is dated Ṣafar 800/October 1397 (Matini, 1997, p. 47). This manuscript of the Kush-nama is composed of 10,129 lines. It contains a number of gaps and a relatively large number of errors, which escaped the notice of the scribe. The text narrates “a community of Iranians who escaped to China due to the Arab invasion; Iranians received maltreatment and hostility of Chinese Emperor in a specific period of time. So, Abtin, commander of the community, wrote a letter to Taehur, Silla’s king, and asked for asylum. Taehur welcomed Iranians. Irano-Sillians fought Chinese king jointly. Abtin married Franak, the daughter of Silla king and the friendship converted to a family transplant.  After a while, Abtin and Franak decided to return back to Iran to secure the country from the Arabs. Faridun, Zoroastrian mythical hero, was born in Iran (the fruit of this marriage) and finally saved the country. According to the text, Faridun contacted his Sillian grandfather through letters and also sent several armies to support Silla against Chinese troops.”  From a specific chapter (verses no. 6000), Silla lost color and disappeared from the text and other tales replaced it. As I (Akbarzadeh, 2014, p. 6) previously noted the coming back of Abtin from Silla to Iran can reflect only a historical wish against the Arabs; it means that wishing to return back as an expected savior (from China-Silla) was achieved mythically in Persian texts but it was never practiced historically. Lack of the information on destiny of those Iranian migrants to Silla was a reason that the tale was interrupted and the story rerouted by other tales. Furthermore, parts of the content can be seen in other Islamic texts (cf. Mojmal-al-Tawarikh, 2010, p. 27). However, the book has three different chapters; the first one focuses on an introduction and the second one on the tales of Hellenic kings like Alexander. The third one or the main chapter stresses on relations between Iran and Silla proper (Akbarzadeh, 2014, p. 2-4). While Master Matini referred to “Silla” as main topic of the text but he suggested the term “Ba/eSilla” of the text (for the term Ba/eSilla> Beh-Silla” see Akbarzadeh and Lee 2018, p. 55) as Japan in another work (1990: 160-177); this suggestion traced his introduction (Kush-nama) by recommendation Mr. Rajabzadeh (1997, p. 75). Also Rajabzadeh (2002, p.  65-71; 2002, p.  82) mistakenly supposed the term Ba/esilla as Japan where he missed Sasanian objects of Gyeongju National Museum, philology, art history and texts studies (Sino-Iranian) (also see Vossoughi 2014, p.  23-45).   2. Methodology This study is based on comparative research by using mythology, text studies, historical records and archaeological evidences. In the study, I have tried to challenge Master Matini’s opinion about a verse (no. 1813) of Kush-nama where he explained the toponym of Kabul as mistake in the manuscript. For this issue, I frequently will refer to historical events of the fall of Sasanian Empire. Meanwhile, in this paper, I stress on the correctness of the verse and prove the text is very correct based on historical events.   3. Discussion: However, a chapter of Kush-nama is dedicated to a military deployment by Chinese king to attack Abtin, Iranian prince, and his troops. In the verse no. 1813, the Chinese King and his troop arrived from (the way) of Kabul to siege and attack Iranians while the text has not cited the toponym Kabul in previous verses. Master Matini, the editor of the text, wrote (footnote no.2 of the page) that “the use of the toponym is incorrect (here) “surly.”  Master Matini explained the toponym as a mistake by the poet! The author believes that the verse is correct based on some events related to the collapse of Sasanian Empire where “southeast of Iran” was entangled with China. For this issue, we are facing with the two important events; the first one was Yazdgird III’s escape to Sistan then to the Central Asia with intention to apply asylum from Chinese king. Secondly, escape of Piruz (Yazdgird’s son) to China, supports of Chinese Emperors of Tang dynasty to him (and other his relatives) against the Arabs. Late Sasanian and Post-Sasanian texts frequently have referred to these two events. Obviously Gaozong, Tang Emperor, welcomed Piruz as the legitimate monarchy of Persia as well as supported him against the Arabs.  Piruz, his son Narse, his brother Bahram and a Sasanian prince by the name Khosrow (?) received Emperors’ supports against the Arabs (Compareti 2009, p.  online). It seems that supports of Chinese Tang Emperor (Gaozong) to Piruz, his stay in Zirang (southeast of Iran), battles over the Arabs, traffics of Sasanian princes between the southeast and China can be comprehensive in the verse. In this specific period southeast of Iran linked with China meaningfully. At this time, the southeast became the cradle of the conflicts with the Arabs, to defend the national identity and secure the country while China was mingled with these issues. Despite Persian sources, Chinese texts also referred to Zirang (Pulleyblank, 1991, p.  online). Most probably, a series of epic Persian texts (Post-Sasanian), where heroes played roles from Sistan to China, can be influenced by those events;  Garshasb in Garshasb-nama, Faridun Tales (Kush-nama and others) and Sam-nama can be cited in support of the claim. The author raises this question as to why heroes such as Faridun, Franak, Garshasb, Zahak and Sam played role in China? Obviously those heroes are related to Zoroastrian resurrection! Other chapters of KN testify the relationship between China and southeast of Iran where the Chinese king asked for help from Mukran king (verse no. 6228). Also I would like to raise this question “who is Firuz, the king of Zabulistan, in Masalik-al-Mamalik?” May I suggest a connection between this king and Piruz, the son of Yazdgird?   4.Conclusion The author believes that expeditions of Sasanian princes from China to the southeast (corridor) are reflected in Chinese king’s campaign in the verse. Also, the time of Hakim Iranshan, Zirang probably was not an important city for political and economic issues. Maybe Kabul overshadowed the toponym this time. Meanwhile, both cities were located in the southeast of Iran. In fact, the coming of a troop from the way which goes to Kabul, cannot be strange. Definitely, the economic situation of Kabul cannot be important for this issue when China and Silla entangled with sacred Zoroastrian elements! Furthermore, the author suggests that meaningful connections between mounts of Sistan and China according to Bundahishn can be influenced by those historical events. While BD knows well paths from Khorasan to China, the text has used two separate terms as “China” and “Chinestan” to describe the Far East. In the late Sasanian to Post-Sasanian texts there is a clear line between two terms which it has never studied (Akbarzadeh, 2020, p.  in print). However, using Persian “be” (toward) in the meaning of Persian “az” (from) frequently is seen in the Persian texts. In Old Persian period (i.e. Avestic text in the north and the Royal Inscriptions in the south) also dative-ablative was a normal function in grammatical structure (Abolghassemi, 1996, p.  287). Clearly the preposition of “be” does not mean “inside” (locative) in the verse.